Pembelajaran Pendidikan Agama Islam Berbasis TPCK Pendekatan Integratif di Era Digital - Aysha Imeylian Suriyani; Ahmad Halid (Yayasan Literasi Altruis Khatulistiwa, 2025)
Digital-based Islamic Religious Education (PAI) learning has become an essential demand in the current technological era, requiring teachers not only to master Islamic material but also to integrate technology, pedagogy, and content (TPCK) effectively. This study examines the application of the TPCK model in PAI learning to enhance learning quality while identifying gaps between ideal standards and classroom reality. Using a qualitative case study approach, data were collected through classroom observations, in-depth interviews with PAI teachers, and analysis of digital teaching materials. The results reveal that digital technologies—such as learning management systems, interactive media, and online assessments—significantly improve student engagement and comprehension of religious concepts. However, limited teacher digital competence, minimal pedagogical innovation, and unequal infrastructure make the implementation of TPCK far from optimal. The study emphasizes the teacher’s central role as the human-in-the-loop in determining material relevance, pedagogical appropriateness, and alignment with students’ spiritual-emotional development. Overall, integrating TPCK with Islamic values, school culture, and digital-era needs creates a more adaptive, interactive, and meaningful PAI learning model. Proper implementation strengthens digital literacy, religious competence, learning motivation, and the development of moderate attitudes, supporting innovation in PAI amid ongoing digital transformation..